Piramun-i hamalat-i rizhim-i `Iraq bih nuqat-i maskuni-yi Iran- tiligramha-yi muhandis Bazargan va duktur Ibrahim Yazdi bih Dabir Kull-i Sazman-i Milal-i Muttahid : (Nihzat-i Azadi-yi Iran)
Regarding the Iraqi attacks on the civilian residential areas of Iran, Mahdi Bazargan and Ibrahim Yazdi's telegrams to the United Nations Secretary General. *Iran Freedom Movement's message of condolence to the beloved fellow citizens.